Pengaruh Strategi Komunikasi Pemasaran Terintegrasi terhadapBrand Awareness pada Museum di Indonesia - Sarjana, Paulus; Harliantara; Maella, Nur Annafi Farni Syam (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2025)
As museums in Indonesia navigate shifting audience preferences, they face growing challenges in attracting younger visitors, largely due to the lack of innovation in marketing communication strategies. The sharp decline in visitor numbers underscores the urgency of adopting a more effective approach, with Integrated Marketing Communication (IMC) emerging as a key strategy. This study examines the impact of IMC on museum brand awareness in Indonesia. Employing a quantitative approach, the research involved 240 Generation Z respondents selected through purposive sampling over a three-month period. Data was analyzed using CB-SEM with AMOS software. Findings reveal that IMC exerts a positive and significant influence on brand awareness, strengthening museum visibility and engagement among younger audiences. The study highlights the need for museums to leverage all IMC elements to create interactive experiences and expand their marketing reach. Museum managers are encouraged to integrate participatory initiatives that resonate with younger generations, ensuring sustained relevance and competitive positioning in the digital era